2017
DOI: 10.1111/jfpp.13500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aromas of instant oolong tea and its counterparts treated with two crude enzymes from Aspergillus niger

Abstract: Sensory evaluation, GC–MS and omission test were used to characterize aromas of noninstant Oolong tea (NIOT), original instant Oolong tea (OIOT) and its counterparts treated by two enzyme extracts from Aspergillus niger. The results showed that OIOT had stronger sweet, fruity, and roasted notes, but weaker grass and floral notes than NIOT. After treated by the crude enzymes extracted from the fermented broth from tea waste (TW) medium, the treated‐OIOT had an improved aroma similar to that of NIOT, due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The present SDE extract and IWT had the characteristic aroma different from those of fresh, slightly brewed whites, but the dominating sweet note seemed similar to that of the aged white tea as reported in previous literatures [9,24]. Although few literatures currently report the effects of instant tea preparation on the aroma of IWT, it has been shown that some factors such as heating and oxidation during instant tea processing could affect the sweet, green and floral odors of tea products [4,25]. For instance, when Pu-erh tea was processed into instant Pu-erh tea, the sweet attribute significantly increased [4].…”
Section: Sensory Evaluationsupporting
confidence: 82%
See 3 more Smart Citations
“…The present SDE extract and IWT had the characteristic aroma different from those of fresh, slightly brewed whites, but the dominating sweet note seemed similar to that of the aged white tea as reported in previous literatures [9,24]. Although few literatures currently report the effects of instant tea preparation on the aroma of IWT, it has been shown that some factors such as heating and oxidation during instant tea processing could affect the sweet, green and floral odors of tea products [4,25]. For instance, when Pu-erh tea was processed into instant Pu-erh tea, the sweet attribute significantly increased [4].…”
Section: Sensory Evaluationsupporting
confidence: 82%
“…For instance, when Pu-erh tea was processed into instant Pu-erh tea, the sweet attribute significantly increased [4]. In addition, when oolong tea was processed into instant oolong tea, the intensities of sweet, fruity and roasted notes increased significantly, but the intensities of floral and grass notes decreased significantly [25]. Therefore, the IWT and SDE extract had a dominated sweet note, which might be attributed to the heating and oxidation process during instant tea preparation.…”
Section: Sensory Evaluationmentioning
confidence: 97%
See 2 more Smart Citations
“…The concentration of 2-pentyl-furan, a fatty acid oxidation product [26], increased by 8.72, 6.44, and 11.63 times after being fermented with SLV, SZP, and SZVP, respectively. Zhang et al [27] found that the enzymes produced by Aspergillus in fermentation of tea increased the content of 2-pentyl-furan, thereby enhancing the floral and grassy odors to improve the sensory quality. Therefore, it is proposed that the metabolites produced by the fermentation strains may increase the 2-pentyl-furan content, where the metabolites generated by B. velezensis may be important.…”
Section: Resultsmentioning
confidence: 99%